Evaluation of an online knowledge translation intervention to promote cancer risk reduction behaviours: findings from a randomized controlled trial - Sarah E. Neil-Sztramko (BMC Cancer, 2019)
Abstract Background Many cancers are preventable through lifestyle modification; however, few adults engage in behaviors that are in line with cancer prevention guidelines. This may be partly due to the mixed messages on effective cancer prevention strategies in popular media. The goal of the McMaster Optimal Aging Portal (the Portal) is to increase access to trustworthy health information. The purpose of this study was to explore if and how knowledge translation strategies to disseminate cancer prevention evidence using the Portal influence participants’ knowledge, intentions and health behaviors related to cancer risk. Methods Adults ≥40 years old, with no cancer history were randomized to a 12-week intervention (weekly emails and social media posts) or control group. Quantitative data on knowledge, intentions and behaviors (physical activity, diet, alcohol consumption and use of tobacco products) were collected at baseline, end of study and 3 months later. Participant engagement was assessed using Google Analytics, and participant satisfaction through open-ended survey questions and semi-structured interviews. Results Participants (n = 557, mean age 64.9) were predominantly retired (72%) females (81%). Knowledge of cancer prevention guidelines was higher in the intervention group at end of study only (+ 0.3, p = 0.01). Intentions to follow cancer prevention guidelines increased in both groups, with no between-group differences. Intervention participants reported greater light-intensity physical activity at end of study (+ 0.7 vs. 0.1, p = 0.03), and reduced alcohol intake at follow u (− 0.2 vs. + 0.3, p < 0.05), but no other between-group differences were found. Overall satisfaction with the Portal and intervention materials was high. Conclusions Dissemination of evidence-based cancer prevention information through the Portal results in small increases in knowledge of risk-reduction strategies and with little to no impact on self-reported health behaviours, except in particular groups. Further tailoring of knowledge translation strategies may be needed to see more meaningful change in knowledge and health behaviours. Trial registration ClinicalTrials.gov NCT03186703, June 14, 2017.